Comparison of growth of Holstein heifers fed100% or 115% of NRC requirements - M. G. Daccarett; J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred and one Holstein heifers from the KSU Dairy Unit were used in this experiment. They were assigned to two treatments in which they were fed either 100% or 115% of the 1988 NRC requirements of energy, protein, major minerals, and major vitamins. Body measurements (height, length, heart girth, weight, body condition scores, and backfat thickness) were recorded. Rations for each group were formulated using the average wt of the heifers. Results suggest that feeding 115% of NRC requirements produces larger frame heifers (without excess body condition), with potential for earlier calving, compared to feeding 100% of NRC requirements.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Growth; NRC Requirements; Expenses